Africa-RISING early win project - Pulse crops as a pathway to increase crop-livestock productivity - Bejiga, G. (International Livestock Research Institute, 2012)
The Africa RISING program (http://africa-rising.net) comprises three linked research-for-development projects, funded by the USAID Feed the Future Initiative. To produce some short-term outputs and to support the longer term objectives of the projects, in 2012 Africa RISING funded several small, short-term projects in each of the regions. Here Geletu Bejiga introduces an ICARDA 'early win' project that aims to improve the productivity of crop-livestock production systems in Ethiopia by integrating pulse crops into systems currently dominated by wheat production